Customer Relationship Management and Brand Image’s Influence on Loyalty through Decision to Stay - Meylani Tuti; Nanda Putri Wicaksono (University of Merdeka Malang, 2021)
The study’s aim is analyzing the influence of management of customer relationship and brand image on loyalty by way of decision to stay. Population of this study was guests who stayed more than twice at Santika Taman Mini Hotel. The sampling technique uses purposive sampling to obtain 243 respondents. The method of data analysis is quantitative descriptive. The quantitative analysis is done by the use of SEM (Structural Equation Modeling). The results of this research indicate that customer relationship management has a significant which gives influence on stay decision , brand image has got influence which is significant on decision to stay, customer relationship management has a significant influence on loyalty, brand image has a significant influence on loyalty, decision to stayhas a significant on loyalty, customer relationship management has an influence that is indirect on loyalty through decision to stay, and brand image has an indirect influence on loyalty through decision to stay.